Answer:
Step-by-step explanation:
y = 2x^2 - 12x +19 Put brackets around the 1st 2 terms. Take 2
y = 2(x^2 - 6x ) + 19 Take 1/2 of the 6 square it and add inside the brackets
y = 2(x^2 - 6 + (6/2)^2) +19 Subtract 2 *9 from the 19. Express 1st 3 terms as ( )^2
y = 2(x- 3)^2 + 19 - 18
y = 2(x - 3)^2 + 1
Answers
y intercept when x = 0 is y = 19
axis of symmetry x = 3
vertex: (3,1)
Graph
graph: red
axis of symmetry: blue
y intercept, vertex: green
Answer:
D
Step-by-step explanation:
1 - 1/4 + 2/5 = 23/20
20/20 - 5/20 = 15/20
15/20 + 8/20 = 23/20
hope this helps! :)
<span>No, it doesn't. To find out if it's a right angled triangle, we use Pythagorean triple. It states that the square of the hypotenuse (the longest side) is equal to the sum of the squares of the opposite and adjacent sides. Obviously, the longest side, which is our hypotenuse is 24. So we want to find out whether the square of our hypotenuse is equal to the sum of the squares of the other two sides i. e 13 and 21.
24^ 2 = 576 ; 13^2 = 169 ; 21^2 = 441;
So is 576 = 169 + 441. An emphatic No: hence the triangle isn't right angled since it doesn't satisfy pythagorean triple.. A^2 is not equal to B^2 + C^2 where a is the hypotenuse and b and c the opposite and adjacent sides.</span>
Answer:
0.07 < 7/50 < 0.5
Step-by-step explanation:
7/50=0.14
=>0.07<0.14<0.5